Filsafat Taoisme dan Quarter Life Crisis: Menggali Relevansi Pemikiran Filsafat Taoisme sebagai Upaya Mencegah Permasalahan Quarter Life Crisis - Asta, Naufal Robbiqis Dwi (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
Quarter-life crisis is a crisis condition that often attacks teenagers who are entering adulthood. This crisis usually makes young people feel doubtful, helpless, afraid, ignorant, empty, and other emotional disturbances such as panic, depression, confusion, frustration, worry, not knowing the direction of their future such as a mate, career, social relations, and so on. so on. To prevent the impact of the quarter-life crisis from happening to teenagers, one way that needs to be done is to study. In this context, studying previous thoughts is also very helpful in preventing quarter-life crises from happening to young people. In addition to getting methods for solving these problems, we can also add insight into the thoughts of previous people. Therefore, this paper will present the relevance of Taoist philosophy to prevent quarter-life crises. In this paper, the author will describe the history and philosophical thought of Taoism. Then from the ideas of Taoism that have been described, its relevance will be drawn to prevent a quarter-life crisis which consists of thoughts about Yin Yang, water as an analogy that describes the flow of Taoism, and the concept of Wu Wei.